UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN FISIKA MELALUI MODEL PEMBELAJARAN PROBLEM POSING PADA SISWA KELAS X.3 SMAN 1 KINALI - Antonius Antonius (JURNAL MANAJEMEN PENDIDIKAN, 2018)
Abstract Based on the result of study of student of Class X.3 SMAN 1 Kinali in sub physics subject Analyzing the influence of calor to a substance, Analyzing Way of heat transfer and Applying Black Principle in solving everyday problem found that result of student study in physics subject still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in the subjects of Physics through Problem Posing Learning Model in Class X.3 SMAN 1 Kinali. This research is a classroom action research. The research procedures in this research include planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 36 students of Class X.3 SMAN 1 Kinali. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that has been raised, it can be concluded that Problem Posing Learning Model can improve student learning outcomes in the subjects of Physics at SMAN 1 Kinali. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 57.75 (Enough) increased to 84.75 (good) with an increase of 27%. Keywords: Learning Outcomes, Physics, Problem Posing Learning Model